Investigation on using oil palm fiber in Porous Asphalt / Tamalkhani Syammaun and Mohamed Rehan Karim - Syammaun, Tamalkhani; Karim, Mohamed Rehan (2012)
This paper presents the results of a preliminary investigation on using oil palm fiber (OPF) in porous asphalt (PA). The samples were prepared with various percentages of OPF (0%, 1%, 2%, 3%, 4% and 5%) by evaluating the weight of bitumen. The laboratory tests included permeability, air abrasion loss and water abrasion loss. The results indicate that the addition of OPF provide a positive effect on the properties of PA. Certain amount of oil palm fiber as an additiveappears to improve resistance to ravelling and stripping. However, adding too much OPF would result in higher abrasion loss value and increase the air voids.